Portugal: a nearshore outsourcing partner - Gonçalves, João Tiago Lopes (2015)
This thesis analyses the attractiveness of Portugal as an European Nearshoring Center by comparing its characteristics and competitiveness vis-à-vis its major competitors. The presence in the European Single Market coupled with a workforce with low costs relative to the qualifications offered, a well-developed transport network and the IT infrastructure quality are indicators of the potential of Portugal to attract Nearshore investments and to become the largest provider of such services to European countries. These intrinsic characteristics of the Portuguese economy were compared with three other well-reputed countries in Outsourcing activities. Comparison of indicators to India and the Philippines reveal the competitive advantages and benefits that Portugal can offer to a Nearshore investment, and will also show areas that need some attention and investment by the Portuguese Government in order to improve the country's competitiveness. Furthermore a comparison with Romania, will demonstrate the positioning of Portugal in the European Nearshoring market. Being Romania one of the possible competitors for Portugal in some Nearshore markets, there will be conducted an analysis of the necessary improvements and areas where Portugal offers stability and added value that put the country in the first line in this type of services. Finally, some statements will be used to demonstrate the real perception of Portuguese competitive advantages by some multinational companies, and understand the reasons why these companies have chosen Portugal as their Nearshoring partner.